From Respect to Insult: The Rise of Derogatory Language in Yoruba Discourse in Aditu Olodumare by D.O Fagunwa. - Ebruphiyo Mamomo Ekanem; Babatunde Bamidele Oyesanya (dialektika kontemporer, 2026)
The Yoruba society, historically, constitutes respect through ‘’èdè ìwà’’ (language and character) that shows honor, politeness and correction, However, contemporary Yoruba discourse shows a marked rise in derogatory / vitriolic utterances or expressions, from parental discipline to youth peer interaction. Existing scholars identified gender bias in proverbs and observes that insults are now fashionable among the younger speakers by which corrective insults became casual slang. Thus, this act begins to weaken the Yoruba traditional language community and institutions. Yet, few or no study have not explained why the sociolinguistic process by which corrective insults became casual slangs, nor the role of weakened traditional institutions in this shift. Using Fairclough’s (2013) theory on Critical Discourse Analysis, this article is filling a gap by drawing a critical discourse analysis, that examines some derogatory expressions purposively selected from Aditu Olodumare by D. O Fagunwa. Analysis reveals three interlocking mechanisms: normalization of identity-based parental insults, collapse of age-grade sanctions on speech, and digital amplification through derogatory language / cruise culture. The article is also poised to expose that Yoruba is undergoing a value shift in language discourse / conversation, not merely lexical change, which indeed calls for family-based language socialization and institutional documentation in order to preserve dignity, respect, and politeness in the Yoruba cultural heritage.